Study on major legal issues and solutions in pandemic treaty negotiations - Weiqi Chen (Frontiers Media S.A., 2024)
In December 2021, WHO's 194 member states began reaching a consensus to start the process of drafting and negotiating a pandemic treaty under the WHO Act. Although there is already a PHEIC system to deal with sudden public health events such as pandemics, the system is not sufficient to deal with global pandemic events. The draft WHO Pandemic Agreement reflects the negotiating process until 24 May 2024. The negotiating team is faced with legal issues such as the treatment of the relationship between the pandemic treaty and the International Health Regulations, the determination of the contracting model, the attribution of the pandemic definition power and the construction of the dispute settlement mechanism. Through a study of the articles of the current draft and a comparative analysis with other treaties, this paper discusses the need to distinguish the functions of the pandemic treaty and the International Health Regulations (IHR), adopt a soft and hard contracting model, establish an open and transparent pandemic determination mechanism, reform the institutional functions of WHO, and establish an effective dispute settlement mechanism in order to solve the above problems. Ultimately, fairness and justice in international public health governance will be achieved.